IMPLEMENTASI UNDANG â UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK DALAM RANGKA MEWUJDUKAN KOTA MALANG SEBAGAI KOTA LAYAK ANAK - PRATAMA, DIPA; DOMAI, TJAHJANULIN; -, RIYANTO (PUBLISIA (Jurnal Ilmu Administrasi Publik), 2016)
Street kids is one among many social issues in Indonesia. Central government already issued Act Number 23 Year 2002 concerning Child Protection, so it needs to be known about the real condition implementation in the field by local government which is Malang City Government. One of Malang City program is Child Friendly City. Implementation of the child protection act expected to give contribution to Malang City programâs achievement. The purposes of this research are to knowing the implementation of child protection act in Malang City by Department of Social Affairs Malang City Government, and knowing the supporting factors and problems that the Department are facing. Type of research method used in this research is descriptive qualitative research. Research data obtained from documentation and unstructured interview with the Department of Social Affairs Malang City Government. Interviews were conducted with the Head of Department and staffs under that selected with purposive sampling based on the subject who understand the issues. Checking the validity of data was using peer debriefingandtriangulation.Â  Analysis data method was using Miles and Huberman qualitative model analysis. Result from the research shows that the child protection act already implemented in street kids countermeasures through the Mayor of Malang Regulation Number 55 Year 2012 and Malang Regional Regulation Number 10 Year 2013 concerning street kids, homeless people, and beggar countermeasures. Supporting factors of the act implementation are (1) Mayor of Malang Regulation Number 55 Year 2012, Local Regulation of Malang City Number 10 Year 2013, (2) Asset that owned by the Department of Social Affairs Malang City Government; Meanwhile the problems that the Department is facing are (1) limited human resources, (2) budgets, (3) and factors that came from street kids themselves.